2015
DOI: 10.1038/nclimate2768
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependence of CO2-enhanced primary production in the European Arctic Ocean

Abstract: The Arctic Ocean is warming at two to three times the global rate 1 and is perceived to be a bellwether for ocean acidification 2,3 . Increased CO 2 concentrations are expected to have a fertilization e ect on marine autotrophs 4 , and higher temperatures should lead to increased rates of planktonic primary production 5 . Yet, simultaneous assessment of warming and increased CO 2 on primary production in the Arctic has not been conducted. Here we test the expectation that CO 2 -enhanced gross primary productio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
68
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(75 citation statements)
references
References 32 publications
(28 reference statements)
6
68
1
Order By: Relevance
“…Another possible reason for the lack of pCO 2 effects is the relatively high incubation temperature. High temperatures have been shown to shift phytoplankton pCO 2 optima to higher levels and could thus dampen OA effects on phytoplankton assemblages (Sett et al 2014;Holding et al 2015;Wolf et al 2017). Although the incubation temperatures were higher than in situ, we argue that our experimental set-up nonetheless reflects a realistic scenario for the current, and certainly the future Arctic Ocean.…”
Section: Assemblages Did Not Respond To Ocean Acidificationmentioning
confidence: 77%
See 4 more Smart Citations
“…Another possible reason for the lack of pCO 2 effects is the relatively high incubation temperature. High temperatures have been shown to shift phytoplankton pCO 2 optima to higher levels and could thus dampen OA effects on phytoplankton assemblages (Sett et al 2014;Holding et al 2015;Wolf et al 2017). Although the incubation temperatures were higher than in situ, we argue that our experimental set-up nonetheless reflects a realistic scenario for the current, and certainly the future Arctic Ocean.…”
Section: Assemblages Did Not Respond To Ocean Acidificationmentioning
confidence: 77%
“…Results from recent field studies have shown a potential for positive OAresponses in primary production and phytoplankton growth (Engel et al 2013;Coello-Camba et al 2014;Holding et al 2015). Increasing temperatures, however, seem to reduce potential benefits of increased CO 2 concentrations (Holding et al 2015), which could be due to a shift in CO 2 optima to higher levels (Sett et al 2014).…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations